Persepsi Mahasiswa Terhadap Jurusan Di Perguruan Tinggi Dan Konsep Diri Dengan Kesesuaian Minat Memilih Jurusan - Masriah, Zakiyatul; Malay, Muhammad Nursalim; Fitriani, Annisa (ANFUSINA: Journal of Psychology, 2018)
This study originated from the idea that Student Perceptions of majors in Higher Education and Self Concepts have a relationship to the Matching Interest in Choosing Departments. The purpose of this study was to find out the relationship between students' perceptions of majors in higher education and self-concept with the suitability of 96 people to choose majors. The sampling technique used is propotional random sampling and then analyzed by multiple regression analysis techniques. The results of this research analysis explain that there is a relationship between students' perceptions of higher education majors and self-concept with the suitability of interest in choosing majors with coefficient of correlation (R) = 0.702 and F = 45,249 with p = 0,000. Then, there is a significant relationship between students' perceptions of majors in higher education with the suitability of their interest in choosing majors, the results of the analysis obtained are the value of rx1y = 0.606 with p = 0,000. Furthermore, there is a significant relationship between self-concept and the suitability of interest in choosing majors seen from the results of calculations obtained by the value rx2y = 0.596 with p = 0,000